A single protein meal increases recovery of muscle function following an acute eccentric exercise bout - Etheridge, T.; Philp, A.; Watt, P. W. (Applied Physiology, Nutrition, and Metabolism, 2008)
Abstract: The purpose of this study was to examine the effects of acute protein ingestion on the recovery of muscle function and markers of muscle damage in the 72 h post eccentric-exercise. Nine recreationally active males recorded quadriceps maximum isometric voluntary contraction (MVC), peak 5 s power output (PPO), and perceived muscle soreness. Plasma creatine kinase (CK) and protein carbonyl (PC) content were measured prior to exercise. Delayed-onset muscle soreness (DOMS) was induced by a 30 min downhill run (-10°) at a target intensity of 75% age-predicted heart rate maximum, immediately followed by ingestion of 100 g protein (containing 40 g essential amino acids; PRO) or placebo (CON) solution. The pre-exercise measures were re-taken in the subsequent 24, 48, and 72 h. CK, PC, and perceived muscle soreness increased significantly following exercise and with each supplement at 24 h. PC and muscle soreness remained elevated at 48 and 72 h (p < 0.05), whereas CK returned to baseline values. No difference between conditions was observed for these measures. Peak MVC significantly declined in CON to -7.9% at 24 h, reaching a nadir of -10% at 48 h (p < 0.05). In the PRO group, MVC remained within pre-exercise values at all time points. PPO followed a similar trend, reaching its nadir of -8.7% at 48 h in CON (p < 0.05), but had recovered in the PRO trial. Ingestion of a single post-exercise protein mixture increases the rate of force and power restoration at 48 h, suggesting potential for protein as an ergogenic aid during the DOMS period.